Multidisciplinary approach to assess the toxicities of arsenic and barium in drinking water - Masashi Kato; Nobutaka Ohgami; Shoko Ohnuma; Kazunori Hashimoto; Akira Tazaki; Huadong Xu; Lisa Kondo-Ida; Tian Yuan; Tomoyuki Tsuchiyama; Tingchao He; Fitri Kurniasari; Yishuo Gu; et al. (Komiyama Printing Co. Ltd, 2020)
Abstract Well water could be a stable source of drinking water. Recently, the use of well water as drinking water has been encouraged in developing countries. However, many kinds of disorders caused by toxic elements in well drinking water have been reported. It is our urgent task to resolve the global issue of element-originating diseases. In this review article, our multidisciplinary approaches focusing on oncogenic toxicities and disturbances of sensory organs (skin and ear) induced by arsenic and barium are introduced. First, our environmental monitoring in developing countries in Asia showed elevated concentrations of arsenic and barium in well drinking water. Then our experimental studies in mice and our epidemiological studies in humans showed arsenic-mediated increased risks of hyperpigmented skin and hearing loss with partial elucidation of their mechanisms. Our experimental studies using cultured cells with focus on the expression and activity levels of intracellular signal transduction molecules such as c-SRC, c-RET, and oncogenic RET showed risks for malignant transformation and/or progression arose from arsenic and barium. Finally, our original hydrotalcite-like compound was proposed as a novel remediation system to effectively remove arsenic and barium from well drinking water. Hopefully, comprehensive studies consisting of (1) environmental monitoring, (2) health risk assessments, and (3) remediation will be expanded in the field of environmental health to prevent various disorders caused by environmental factors including toxic elements in drinking water.